Hebrews a little library of exposition with new studies - Inge, W.R.; Goudge, H.L. (London, UK Cassell, 1926)
Includes bibliographical references.
Donated by Mr W. Forshaw
Keywords: Bible. N.T. Hebrews -- commentaries